Evaluation of related factors to repeated radiographs in radiology centers of Hamadan‍‍‍‍ hospitals - Manoochehri Khoshinani, Hamed; Heidari, Samira (Archives of Advances in Biosciences, 2014)
Repeating X-ray radiographs, as a common problem in radiology units, represent additional, non-billable costs due to increased film, chemistry, and equipment use as well as increased personnel time. Furthermore, patients receive additional radiation exposure from repetitions and must remain on the premises until the second exam is completed. Compounding the overt negative financial impact on the department is an increased burden on the waiting room and support staff, and a decrease in service quality. This study was designed to measure the radiograph repeat rate for Beesat and Farshchian hospitals in Hamadan, Iran. In this cross-sectional study the repeat rate was documented over the course of 3 months in Beesat and Farshchian hospitals. Regarding to personnel code, repeat rate were measured weekly for each staff and a questionnaires including sex, age, work experience, education level as well as shift numbers during 3 months were completed for each one. Collected data was analyzed by SPSS#20 using Chi-Squar and two sample T-test. Based on our results. The x-ray repeat rate was 3.8% for both studied hospitals. Repeat rate was also calculated for each hospital which showed 3.6% for Beesat and 5.4% for Farshchian. The highest repeat rate was documented for students and male personnel. The repeat rate for Beesat and Farshchian hospitals were acceptable according to published ones. The highest repeat rate in students and the negative relationship between work experience and the repeat rate suggests the need for close monitoring and more training for new staff especially students.